PEMBUATAN KERTAS DARI LIMBAH KULIT MATOA DAN AMPAS TEH DENGAN PERBEDAAN KONSENTRASI NaOH - Supriyono, Arif (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The development of science and technology in the current era of globalization causes the need for paper to continue to increase every year. The main raw material for making paper is cellulose, which is derived from wood. It is estimated that 70% of the raw material needed for pulp and paper production comes from natural forests. The increasing demand for pulp and paper production capacity means more and more illegal logging of trees through illegal practices by exploiting natural forests so that it can cause damage. This has a negative impact on the sustainability of forest resources and threatens the living things in it. In order to reduce these negative impacts, alternative raw materials are needed in paper making. Renewable raw materials that canreplace the role of wood in paper making are matoa skin waste and tea dregs. Matoa fruit peel has potential as a substitute for paper making because it has a high cellulose content of about 50%, while the cellulose content in tea pulp is around 37%. This study consisted of 3 treatments, namely P1 (50 grams of matoa skin + 50 grams of tea dregs + NaOH 2.5%), P2 (50 grams of matoa skin + 50 grams of tea pulp + NaOH 3.0%), P3 (50 grams of peels matoa + 50 grams of tea dregs + NaOH 3.5%). This study consisted of 5 test parameters, namely, water content, cellulose content, lignin content, tensile strength, and tearing power.